Corticospinal Tract and Pontocerebellar Fiber of Central Pontine Myelinolysis - Min, Yong (Korean Academy of Rehabilitation Medicine, 2012)
Central pontine myelinolysis is a rare neurologic disorder that is defined by demyelination of longitudinally descending tracts and transversly crossing fibers in the basis pontis. Frequently observed clinical manifestations of this disorder include sudden weakness, dysphagia, loss of consciouness and locked-in syndrome. However, there have been a few studies that reported a benign course of this disease, which include cerebellar signs, such as ataxia, intention tremor, and dysarthria. Here we report on a 53-year-old male with a history of liver cirrhosis who showed the cerebellar type of central pontine myelinolysis. The patient was diagnosed with central pontine myelinolysis based on clinical presentations and magnetic resonance imaging findings after a liver transplantation. Conventional magenetic resonance imaging (MRI) revealed the preservation of the corticospinal tract and abnormal pontocerebellar fibers. However, these findings were not sufficient to define the pathophysiology of our patient. Electrophysiologic analysis and diffusion tensor imaging (DTI) were performed to investigate cerebellar signs in this case. Delayed central motor conduction time (CMCT) to the tibialis anterior muscle with transcranial magnetic stimulation (TMS) was observed, which indicated demyelination of the corticospinal tract. Also, diffusion tensor imaging showed abnormal pontocerebellar fibers, which might have been caused by cerebellar dysfunction in our patient. A combination of TMS and DTI was also used to determine the pathophysiology of this disease.